Controls of hydrothermal fluid flow and gold mineralization in the Sheba-Fairview Complex, Barberton Greenstone Belt, South Africa - Jones, Caitlin (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.